Analysis of Students’ Errors in Solving the Circle Equation of Class XI Multimedia Students at SMKN 3 Pekanbaru - Dewi Yuliani; Kartini (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2020)
The inability of students to solve problems will result in errors in solving them. This study aims to describe students' errors in the circle equation material and the factors that cause errors in class XI SMKN 3 Pekanbaru and solve math problems related to circle equation material. This research is descriptive research. The subjects in this study were 36 students of class XI SMKN 3 Pekanbaru. The data collection technique was carried out by means of a learning outcome test which consisted of instruments describing the circle equation. As for the percentage of errors made by students, namely students who made fact errors as much as 29% due to the lack of accuracy of the students in writing the symbols of the circle equation, the students made 23% misconceptions because the students did not understand the questions well so that students are random in determining the formula used to solve the problem, students made a principle error of 16% because the students were careless in determining the formula to solve the questions, students make operating errors as much as 32% because students are not careful in doing algebraic operations and are in a hurry to work on the problem.